2020
DOI: 10.1021/acsami.9b20939
|View full text |Cite
|
Sign up to set email alerts
|

Cell–Cell Adhesion-Driven Contact Guidance and Its Effect on Human Mesenchymal Stem Cell Differentiation

Abstract: Contact guidance has been extensively explored using patterned adhesion functionalities that predominantly mimic cell–matrix interactions. Whether contact guidance can also be driven by other types of interactions, such as cell−cell adhesion, still remains a question. Herein, this query is addressed by engineering a set of microstrip patterns of (i) cell–cell adhesion ligands and (ii) segregated cell–cell and cell–matrix ligands as a simple yet versatile set of platforms for the guidance of spreading, adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 75 publications
1
21
0
1
Order By: Relevance
“…Previous studies have shown that cell adhesion plays a vital role in a number of pathological processes, including the recirculation and movement of leukocytes, 39 cell differentiation, 40 and the activation of and communication between immune cells. 41 Furthermore, changes in the levels of adhesion molecules and cytokines have been detected in diabetic nephropathy and reported to represent vital mediators of injury in several types of glomerulonephritis and tubulointerstitial nephritis, thus underscoring their diagnostic roles in this renal microvascular complication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cell adhesion plays a vital role in a number of pathological processes, including the recirculation and movement of leukocytes, 39 cell differentiation, 40 and the activation of and communication between immune cells. 41 Furthermore, changes in the levels of adhesion molecules and cytokines have been detected in diabetic nephropathy and reported to represent vital mediators of injury in several types of glomerulonephritis and tubulointerstitial nephritis, thus underscoring their diagnostic roles in this renal microvascular complication.…”
Section: Discussionmentioning
confidence: 99%
“…When subjected to luminal shear flows, focal adhesions in ECs undergo a rapid remodeling and alignment in the direction of the flow within a few minutes . Similarly, focal adhesions play key roles in sensing spatial features of the ECM, both independently or in conjunction with the cell–cell interactions. , For example, micrometer-sized patterns induce the reorganization of the actin cytoskeleton and FAs to orient cell movements and migrate. , …”
Section: Introductionmentioning
confidence: 99%
“…30 Similarly, focal adhesions play key roles in sensing spatial features of the ECM, both independently or in conjunction with the cell−cell interactions. 31,32 For example, micrometer-sized patterns induce the reorganization of the actin cytoskeleton and FAs to orient cell movements and migrate. 33,34 At the cell−cell interface, endothelial adherens junctions (EAJs) serve as the adhesive structures mediating the physical connection and the transmission of biomechanical signals between ECs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Adhesion between solid materials is crucial in several fields of biology, science, and technology, such as cellular adhesion and contact mechanics. It is caused by intermolecular forces, like hydrogen bonding and van der Waals forces . These mechanisms are taking place up to a distance of 0.1–0.4 nm , and, thus, require nanoscale contact (NSC) between the adhering surfaces. , As a result, an increase in nanoscale contact area (NSCA) leads to an increase in adhesion between surfaces. …”
Section: Introductionmentioning
confidence: 99%